Investigation of Mixing Dynamics of a Pilot-Scale Twin-Paddle Blender Containing Non-Spherical Particles - Behrooz Jadidi; Mohammadreza Ebrahimi; Farhad Ein-Mozaffari; Ali Lohi (Engineering Proceedings)
An in-depth analysis of the flow patterns and mixing dynamics in a twin-paddle blender with bi-disperse non-spherical particles was investigated using the discrete element method (DEM) and experiments. This study aimed to explore the mixing efficiency of a twin-paddle blender containing two different shapes of non-spherical particles. The study focussed on the demonstration of the applicability of the GPU-based DEM model. To achieve this, calibration tests were performed using a classical rotary drum to validate the accuracy of the DEM model. The next step was to examine the impact of various operating parameters on the mixing performance, such as impeller rotational speed. The relative standard deviation (RSD) was employed as a measure of mixing performance. Results revealed that the rotational speed of the impellers had a significant impact on the mixing performance.